The Debt Maturity Issue in Access Pricing1. Issue 290 (18th March 2014) - Davis, Kevin
<x xml:space="preserve">Abstract</x> There has been substantial debate and disagreement over the appropriate debt maturity used in determining the cost of debt for use in access pricing decisions in Australia. Some regulators have used a debt maturity corresponding to the length of the regulatory reset period (typically five years). Others have used a longer maturity based on the argument that the assets being financed are long‐lived. In this article it is demonstrated that under the current Australian approach, to meet the objectives of access pricing, the assumed debt maturity should be set equal to the term of the regulatory reset period. Whether practical debt management difficulties for access providers suggest that an alternative approach, placing more emphasis on their actual debt costs (as occurs in some other jurisdictions) should be considered, is also discussed.